Characteristics of ice rises and ice rumples in Dronning Maud Land and Enderby Land, Antarctica - Vikram Goel; Kenichi Matsuoka; Cesar Deschamps Berger; Ian Lee; Jørgen Dall; René Forsberg (Journal of Glaciology, 2020)
Ice rises and rumples, locally grounded features adjacent to ice shelves, are relatively small yet play significant roles in Antarctic ice dynamics. Their roles generally depend upon their location within the ice shelf and the stage of the ice-sheet retreat or advance. Large, long-stable ice rises can be excellent sites for deep ice coring and paleoclimate study of the Antarctic coast and the Southern Ocean, while small ice rises tend to respond more promptly and can be used to reveal recent changes in regional mass balance. The coasts of Dronning Maud Land (DML) and Enderby Land in East Antarctica are abundant with these features. Here we review existing knowledge, presenting an up-to-date status of research in these regions with focus on ice rises and rumples. We use regional datasets (satellite imagery, surface mass balance and ice thickness) to analyze the extent and surface morphology of ice shelves and characteristic timescales of ice rises. We find that large parts of DML have been changing over the past several millennia. Based on our findings, we highlight ice rises suitable for drilling ice cores for paleoclimate studies as well as ice rises suitable for deciphering ice dynamics and evolution in the region.